A Novel Stress Tensor-Based Failure Criterion for Peridynamics - Daniele Dipasquale; Arman Shojaei; Soemsak Yooyen (My University, 2020)
Peridynamic theory has recently shown to be a versatile tool for simulating complex phenomena related to the fracture and fragmentation of structural and composite materials. We introduce a novel failure criterion based on the classic stress tensor which takes inspiration from an approach proposed in the literature. Differently from the classic critical stretch-based failure criterion used in peridynamics, our approach takes into account the total elastic energy stored in the bond allowing to predict with more accuracy problems that involve mixed-mode I-II fracture. In order to show the effectiveness of the proposed failure criterion, a benchmark fracture problem is analyzed showing a good agreement with the experimental results and the numerical results obtained with other numerical methods.
Keywords: Peridynamics; Benchmark (surveying); Material failure theory; Numerical methods in engineering